2004
DOI: 10.1021/la034940j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Characterization of Surface Sol−Gel Processes

Abstract: 3-Mercaptopropyl)trimethoxysilane (MTS) forms a unique film on a platinum substrate by self-assembly and sol-gel cross-linking. The gelating and drying states of the self-assembled MTS sol-gel films were probed by use of electrochemical and spectroscopic methods. The thiol moiety was the only active group within the sol-gel network. Gold nanoparticles were employed to detect the availability of the thiol group and their interaction further indicated the physicochemical states of the sol-gel inner structure. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Additionally, the presence of SH group in the MPS gel is verified by the S-H stretching band observed at 2555 cm À1 [37,40]. The S-H band indicates that only a fraction of thiol groups reacts with Au and the polymer is composed of Si-O-Si network with OH and C 3 H 6 SH functional groups.…”
Section: Au|mpsmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, the presence of SH group in the MPS gel is verified by the S-H stretching band observed at 2555 cm À1 [37,40]. The S-H band indicates that only a fraction of thiol groups reacts with Au and the polymer is composed of Si-O-Si network with OH and C 3 H 6 SH functional groups.…”
Section: Au|mpsmentioning
confidence: 85%
“…This was achieved by sol-gel processing of methyltrimethoxysilane (MTMOS) on gold surface premodified with 3-mercaptopropyltrimethoxysilane (MPS). Although, the self assembly of the latter compound on Au [34][35][36], Ag [36] or Pt surface [37] or its application for three dimensional film preparation on gold [38,39] or platinum [40] was already reported according to our knowledge it was not previously used for anchoring silicate film based on other precursor.…”
Section: Introductionmentioning
confidence: 99%
“…High overall porosity, good accessibility of pores, high active surface area and possibility to maintain a variety of materials make silica aerogels a potential matrix for the design of biological sensor [197] [245,246]. Ayers et al [196] in their pioneering work, utilized photoluminescence silica-based aerogel as an active element Power et al [65] reported biosensor based on wetted mesoporous silica aerogels, which can be integrated as a scaffold for immobilization and growth of bacteria with a special biological function of their porosity for detection and collection of aerosol viral particles.…”
Section: Aerogel For Biosensing Applicationsmentioning
confidence: 99%
“…(3-Mercaptopropyl) trimethoxysilane (MPTS) is known to form a 3-D structure and is full of thiol tail groups from the hydrolysis process. 23 The thiol group has a strong affinity to Au through the cleavage of the S-H bonds. 24 Because of these thiol groups distributed throughout the network, the colloidal gold nanoparticles can be conveniently self-assembled on the thiol groups which present both inside and on the surface of the network.…”
Section: Introductionmentioning
confidence: 99%